A Study of Entrepreneurial Intention of Students of Jamia Millia Islamia During COVID - 19 Period - Siddiqui, Daniya; Ahmad, Naseeb (AMC Indian Journal of Entrepreneurship, 2021)
Entrepreneurship is one of the prominent factors for the development of a nation. The government of India is rigorously promoting innovation, startups, and entrepreneurship and is allocating huge funds to foster the growth of the entrepreneurial environment. To encourage students to explore entrepreneurship as a career option, a variety of organizations, schemes, and projects are offering a support system and connecting industries, institutions, and skill development programs. Jamia Millia Islamia is the Central University in India that is promoting entrepreneurship and is providing students with relevant support for innovative startups. The entrepreneurial intention of students is one of the important factors to inculcate entrepreneurial behavior in students. This research paper was an attempt to measure the entrepreneurial intention of students of Jamia Millia Islamia during COVID-19. A sample of 203 students of Jamia Millia Islamia was taken. Multiple regression was conducted to know the impact of entrepreneurial behaviour, business opportunities during COVID-19, and entrepreneurial environment in India on the entrepreneurial intention of students. The findings may help educators, administrators, and policymakers to promote entrepreneurship among students.